Community-acquired pneumonia in primary care: clinical assessment and the usability of chest radiography. (2nd January 2016) - Moberg, A.B.; Taléus, U.; Garvin, P.; Fransson, S.-G.; Falk, M.
Abstract: Objectives: To investigate the diagnostic value of different clinical and laboratory findings in pneumonia and to explore the association between the doctor's degree of suspicion and chest X-ray (CXR) result and to evaluate whether or not CXR should be used routinely in primary care, when available.Design: A three-year prospective study was conducted between September 2011 and December 2014.Setting: Two primary care settings in Linköping, Sweden.Subjects: A total of 103 adult patients with suspected pneumonia in primary care.Main outcome measures: The physicians recorded results of a standardized medical physical examination, including laboratory results, and rated their suspicion into three degrees. The outcome of the diagnostic variables and the degree of suspicion was compared with the result of CXR.Results: Radiographic pneumonia was reported in 45% of patients. When the physicians were sure of the diagnosis radiographic pneumonia was found in 88% of cases ( p < 0.001), when quite sure the frequency of positive CXR was 45%, and when not sure 28%. Elevated levels of C-reactive protein (CRP) ≥ 50mg/L were associated with the presence of radiographic pneumonia when the diagnosis was suspected ( p < 0.001).Conclusion: This study indicates that CXR can be useful if the physician is not sure of the diagnosis, but when sure one can rely on one's judgement without ordering CXR. Key points: There are different guidelines but no consensus on how to manage community-acquired pneumonia in primary care. When the physician is sure of the diagnosis the judgement is reliable without chest X-ray and antibiotics can be safely prescribed. Chest X-ray can be useful in the assessment of pneumonia in primary care, when the physician is not sure of the diagnosis.